An interesting case of primary squamous cell carcinoma of the colon with synchronous metastatic adenocarcinoma. Issue 6 (6th October 2014) - Rajan, Ruben; Baqar, Ali; Menon, Tulsi
<x xml:space="preserve">Abstract</x> We present a case of primary squamous cell carcinoma of the colon with synchronous metastatic adenocarcinoma. This case highlights the poor prognosis of these late presenting cancers. Furthermore the unusual dual pathology raises questions about its potential etiology. <boxed-text content-type="graphic" id="ccr3127-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>